2014
DOI: 10.1093/jmcb/mjt053
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Wnt signaling at the neuroimmune interface for dopaminergic neuroprotection/repair in Parkinson's disease

Abstract: During the past three decades, the Wingless-type MMTV integration site (Wnt) signaling cascade has emerged as an essential system regulating multiple processes in developing and adult brain. Accumulating evidence points to a dysregulation of Wnt signaling in major neurodegenerative pathologies including Parkinson's disease (PD), a common neurodegenerative disorder characterized by the progressive loss of midbrain dopaminergic (mDA) neurons and deregulated activation of astrocytes and microglia. This review hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 173 publications
(308 reference statements)
1
109
0
1
Order By: Relevance
“…Wnt signals are transduced by canonical and non-canonical pathways, relying on the expression profiles of Wnt ligands, coreceptors, the Fzd family receptors, Wnt antagonists, and the activity of cytoplasmic Wnt signaling regulators [18]. Evidence has shown that the Wnt/β-catenin signaling pathway is involved in PD pathogenesis [33]. In vivo and in vitro studies have revealed that Wnt3 is present in the hippocampal neurogenic niche and regulates newborn neurogenesis in the dentate gyrus [20].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signals are transduced by canonical and non-canonical pathways, relying on the expression profiles of Wnt ligands, coreceptors, the Fzd family receptors, Wnt antagonists, and the activity of cytoplasmic Wnt signaling regulators [18]. Evidence has shown that the Wnt/β-catenin signaling pathway is involved in PD pathogenesis [33]. In vivo and in vitro studies have revealed that Wnt3 is present in the hippocampal neurogenic niche and regulates newborn neurogenesis in the dentate gyrus [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, Wnt1 becomes expressed in reactive astrocytes upon injury of this region (reviewed in L'Episcopo et al . ). Thus, it is tempting to speculate that dopaminergic neurons within DA 1 (specifically subtype DA 1A ) are more vulnerable to toxic insults (and perhaps to the PD disease process) given that they do not express Fzd1.…”
Section: Diversity Of Neurons In the Ventral Mesencephalic Dopaminergmentioning
confidence: 97%
“…In this family, BDNF appears to exhibit the most potent activity in neural development and neuroplasticity (Mitchelmore and Gede 2014; Nosheny et al 2005). BDNF has also been implicated in the etiology of diverse types of neurological disorders (Harte-Hargrove et al 2013), such as depression (Manosso et al 2015; Stuke et al 2012), schizophrenia (Notaras et al 2015; Reinhart et al 2015; Zhang et al 2016), Alzheimer’s disease (AD) (Phillips et al 1991; Tapia-Arancibia et al 2008), Huntington’s disease (HD) (Borrell-Pages et al 2006), and Parkinson’s disease (PD) (L’Episcopo et al 2014). Remarkably, many recent studies have shown that BDNF is emerging as a particularly important player in neuropathic pain (Coull et al 2005; Inoue 2009; Itokazu et al 2014).…”
Section: Instructionmentioning
confidence: 99%